2004
DOI: 10.1358/mf.2004.26.5.831326
|View full text |Cite
|
Sign up to set email alerts
|

A panel study on the effects of a Chinese medicinal suppository, Vigconic VI-28, on insulin-like growth factor 1 and homocysteine in healthy men

Abstract: Metadata onlyChanges in serum homocysteine (Hcy), often related to stroke and vascular dementia, are negatively correlated with changes in serum insulin-like growth factor 1 (IGF-1) and growth hormone (GH) replacement decreases Hcy levels in men with GH deficiency. Very little information on the effects of Chinese medicines on GH and Hcy is available in the literature published in English. In this study, the effects of a Chinese medicine suppository, Vigconic VI-28 (VI-28), consisting of concentrated extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
2
7
1
1
Order By: Relevance
“…Also reported was the beneficial regulatory effect of a Chinese medicinal suppository, Vigconic VI-28 which is similar in composition and action to Vitalliver (a Chinese medicinal suppository engaged in the present study), on Hcy and IGF-1, and their relationship among 36 healthy aging Chinese males, and an apparent association of hyperhomocysteinemia (Hcy ≥ 13.0 µmol/L) with decreased IGF-1 was observed (Chui et al, 2004). The aim of the present study was to investigate whether similar regulatory effects of Vitalliver on Hcy and IGF-1 could be found in chronic hepatitis B patients without liver cirrhosis.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Also reported was the beneficial regulatory effect of a Chinese medicinal suppository, Vigconic VI-28 which is similar in composition and action to Vitalliver (a Chinese medicinal suppository engaged in the present study), on Hcy and IGF-1, and their relationship among 36 healthy aging Chinese males, and an apparent association of hyperhomocysteinemia (Hcy ≥ 13.0 µmol/L) with decreased IGF-1 was observed (Chui et al, 2004). The aim of the present study was to investigate whether similar regulatory effects of Vitalliver on Hcy and IGF-1 could be found in chronic hepatitis B patients without liver cirrhosis.…”
Section: Introductionsupporting
confidence: 58%
“…In the present study, however, hyperhomocysteinaemia was not observed at baseline nor during the 3-month treatment period. Among the 40 chronic HBV patients, only three male patients (7.5%) had baseline Hcy levels greater than 13.0 µmol/ L, a cut-off value applied to differentiate the healthy subjects involved in the anti-aging study using VI-28 as described previously (Chui et al, 2004). However, trends of increase in IGF-1/IGFBP-3 were not observed in these three patients after treatment with Vitalliver.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, several peer-reviewed reports have suggested that a novel TCM formula, denoted as VI-28, possessed anti-aging activities (Chui et al, 2004;Mak et al, 2004). A pilot clinical trial showed that VI-28 could exert a regulatory effect on serum homocysteine (Hcy) and insulin-like growth factor 1 (IGF-1), suggesting a possible reduction in stroke and vascular dementia in 36 male subjects (Chui et al, 2004). VI-28 was also shown to enhance significantly Radix Salviae miltiorrhizae (12%), Semen Allii (12%), Fructus Cnidii (8%), Fructus Evodiae (8%) and Rhizoma Kaempferiae (10%).…”
Section: Introductionmentioning
confidence: 99%
“…За результатами клінічних спостережень, зростання рівня гомоцистеїну супроводжується зниженням рівня IGF-1 в сиро-ватці крові практично здорових чоловіків [15] та осіб похилого віку [16]. З іншого боку, зменшен-ня рівня IGF-1 може виявитись самостійним чинником, що індукує розвиток ГГЦ за НАжХП, оскільки in vitro встановлено здатність цього ростового фактора підвищувати активність ме-тіонінсинтетази [17].…”
unclassified